Learning for life or for pleasure - Administrador, Diobaldo César; Heredia Gutiérrez, Diobaldo César; Administrador, Diobaldo César (Corporación Universitaria Americana, 2011)
The teaching-learning process corresponds to a communicative systemcorresponds to a communicative system par excellencethat requires a high dose of love thatguarantees the enjoyment or enjoyment of the participants, in a satisfactoryof search and satisfactory discovery.In order to give it a high degree of quality, the participation of students and teachers isthe participation of more enterprising and critical students and teachersmore enterprising and critical and less academic or dependentand critical and less academic or dependent, thus autonomous learning is key.the achievement or goal, then, is students who learn as if they were going to teach.students who learn as if they were going to teach and teachers who areproactive and expert in the subjects they teach.they teach.